OVERCOMING VITAMIN B12 DEFICIENCY IN VEGAN DIET - Sridevy; Baby, Prassanna (Journal of Health and Allied Sciences NU, 2014)
Vitamin B12 is a crystalline compound essential to a number of micro-organisms and animals, including humans. So far as is known it is not present in higher plants. Pure vegetarian food is nearly free from vit. B12. It is a nutrient that needs attention in vegan diet. Vegetarians are at risk for vitamin B(12) (B12) deficiency due to suboptimal intake. Dietary deficiency of vitamin B12 due to vegetarianism is increasing and causes hyperhomocysteinemia Areas for research include intermittent vitamin B12 supplement dosing and better measurements of the bioavailability of B12 in fermented vegetarian foods and algae. The goal of the present literature review was to create an awareness among the vegans to identify the vegetarian sources of Vitamin B12 and to incorporate them into their daily diet.
Keywords: vegan; fortified sources; macrocytic anemia; perinicious anaemia